Knowledge management systems for decision makers in public universities Malaysia - Md. Daud, Ruzaif Adli; Hassan, Shahizan (2008)
Knowledge is identified as the crucial asset of an organization especially in the Higher Learning Institutions (HLI) and universities. These institutions are recognized in the knowledge business due to their involvement in the knowledge creation and dissemination processes.The implementation of Knowledge Management Systems (KMS) for decisions makers in Public Universities in Malaysia (PUM) is inevitably challenging Most PUM are not structured for the application of KMS and do not have a unified implementation mode l in place. Therefore, the main objective of this research is to develop a KMS implementation model for decision makers in PUM. To achieve the objectives of this study the triangulation method was used.This paper also includes a brief description on research population, validation, data analysis and KMS implementation model for decision makers in PUM.